2018
DOI: 10.1155/2018/9108483
|View full text |Cite
|
Sign up to set email alerts
|

Partial Inhibition of HO‐1 Attenuates HMP‐Induced Hepatic Regeneration against Liver Injury in Rats

Abstract: We found better liver graft regeneration with hypothermic machine perfusion (HMP) compared with static cold storage (SCS) for the first time in our pilot study, but the underlying mechanisms are unknown. Upregulated heme oxygenase- (HO-) 1 expression has been reported to play a pivotal role in promoting hepatocyte proliferation. Here, we evaluated the novel role of HO-1 in liver graft protection by HMP. Rats with a heterozygous knockout of HO-1 (HO-1+/−) were generated and subjected to 3 h of SCS or HMP pre-ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…AKT is a central signaling molecule involved in a variety of intracellular signal transduction pathways and plays diverse cellular roles, including cellular growth, proliferation, metabolism, survival, angiogenesis, and migration [35]. Previous studies have reported that ER stress-induced hepatocyte death is dependent on AKT inhibition [36], and activation of the AKT pathway participates in the protective effects of liver injury [37,38]. In this context, we examined the activity of the AKT pathway following cold exposure.…”
Section: Discussionmentioning
confidence: 99%
“…AKT is a central signaling molecule involved in a variety of intracellular signal transduction pathways and plays diverse cellular roles, including cellular growth, proliferation, metabolism, survival, angiogenesis, and migration [35]. Previous studies have reported that ER stress-induced hepatocyte death is dependent on AKT inhibition [36], and activation of the AKT pathway participates in the protective effects of liver injury [37,38]. In this context, we examined the activity of the AKT pathway following cold exposure.…”
Section: Discussionmentioning
confidence: 99%
“…And HO-1 is involved in cellular protection by decreasing oxidative stress, reducing cellular apoptosis and inflammatory response. The cells showed more oxidative stress levels after the knockdown of HO-1, which contributed to the attenuation of SOD activity[ 12 , 42 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The concept of improved peripheral sinusoidal flow and microvascular protection through the HOPE concept is also interesting [ 83 , 84 ]. In the context of LDLT, existing experimental studies demonstrated an improved growth and earlier entrance into the cell-cycle for quicker liver regeneration after hypothermic perfusion [ 85 , 86 , 87 ]. The combination of microvascular protection and better mitochondrial metabolism with more energy (ATP) levels may serve as an additional protective effect inducing better liver function and accelerated regeneration.…”
Section: Discussionmentioning
confidence: 99%